Recurrent terminal ventricle cyst: a case report. Issue 11 (11th November 2021) - Baig Mirza, Asfand; Visagan, Ravindran; Boardman, Timothy; Murphy, Christopher; Al-Ali, Bilal; Kellett, Christopher; Grahovac, Gordan
Abstract: The terminal ventricle (TV) of Krause is a rare cystic dilation of the conus' central canal. Due to limited understanding surrounding its pathophysiology, optimal management remains controversial. We report a 25-year-old female presenting with acute paraparesis. Magnetic resonance imaging spine revealed a cystic conus medullaris lesion in keeping with an incidental TV cyst. However, the patient experienced a rapid resolution of symptoms. We hypothesize that the TV cyst spontaneously ruptured and auto-decompressed. To our knowledge, this is the first reported case of an enlarging symptomatic TV cyst with spontaneous rupture and resolution of symptoms, highlighting the variable natural history of this condition.